The relationship between serum vitamin D levels and childhood atopic dermatitis (Annals of Medical Research, 2021)
Aim: We aimed to evaluate serum vitamin D levels among children who have atopic dermatitis (AD) and to determine relationship with its clinical features and laboratory.Material and Methods: One hundred twenty children (66 B, 54 G) with AD, aged between 1-16 years, followed up from Pediatric Allergy Outpatient Clinic were enrolled. Family history of atopy, comorbid allergic diseases, allergy skin prick tests, serum total peripheral blood eosinophil counts, IgG, IgA, IgM, IgE levels, were recorded. AD severity was determined by using Scoring Atopic Dermatitis (SCORAD) index. The serum 25(OH)D vitamin levels were studied with HPLC method.Results: The mean serum total IgE level was 557 ± 425.3kU/L and mean blood eosinophil count was 557 ± 425.3 mm3. The meanserum 25(OH) vitamin D level was 28.42 ± 10.56 ng/ml. One of the patients (0.83%) had severe vitamin D deficiency, 16 (13.3%) had deficiency and 55 (45.8%) had insufficiency. Serum vitamin D level was normal in 48 (40 %) patients. According to SCORAD index, mean serum vitamin D level was higher in patients with mild AD (32.18 ± 7.91 ng/ml) than in patients with moderate disease(28.79 ± 11.02 ng/ml) or in patients with severe AD (23.78 ± 8.92 ng/ml)(p0,05).Serum 25(OH)D levels were inversely correlated with SCORAD index values (r =-0.273, p= 0.003). Conclusions: In this study, we showed a reverse correlation between serum 25(OH)D vitamin level and atopic dermatitis severity. Vitamin D deficiency should be thought in unresponsive AD cases.
Keywords: Atopic dermatitis; childhood; IgE; SCORAD; vitamin D